Implementation of PJBL-STEAM to Improve Science Process Skills in Vibration and Wave Material at Vocational School - Iferelda Irene; Stepanus Sahala Sitompul; Erwina Oktavianty (Berkala Ilmiah Pendidikan Fisika, 2024)
Education becomes the sword of poverty by improving the quality of people in a country. Therefore, various research in education continues to be carried out to get all the best recommendations and evaluation material in the field of education, as done in this study. This study aims to determine how applying the PjBL-STEAM improves students' science process skills on vibration and wave material at SMK PGRI Pontianak. The form of this research is a quasi-experiment that is a pre-experimental design type, one-group pretest-posttest design. The research sample was class X students at SMK PGRI Pontianak, totalling 25 people. The instruments used were tests, questionnaires, and interviews. This study used descriptive statistical analysis techniques and inferential statistical analysis. In the pretest, 40% of students had science process skills in the unskilled category, and 48% were in the less skilled category. In the post-test, 76% of students' science process skills were in the highly skilled category, and 12% were in the skilled category. Then, based on the results of the Wilcoxon Test, the value of Asymp. Sig (2-Tailed) of 0.000 (r < 0.05) shows that there is a difference in the science process skills of students in the pretest and post-test, with the level of effectiveness in the high category (3>0.7). Based on the response questionnaire data, the result of students' response analysis to the learning process is that 95% of students gave very good responses, and 5% were categorised as good. The research concludes that applying the PjBL-STEAM effectively improves students' science process skills on vibration and wave material at SMK PGRI Pontianak.